Plan de negocios para una empresa productora y comercializadora de pulpa de frutas congelada 100% natural, ubicada en la ciudad de Armenia “Frutipulpas del Quindío S.A.S” (2010)
Frutipulpas del Quindío S.A.S., will be located in the municipality of Armenia, Quindío, in order to produce and commercialize frozen fruit pulp 100% natural, offering a product of excellent quality in the market to through supermarkets, mini markets, restaurants, coffee shops, school restaurants and neighborhood stores. This company will provide fruit pulp under strict and adequate hygiene processes, minimizing polluting risks, as well as using natural raw materials that guarantee the consumer a food with appearance, aroma and pleasant texture, contributing so much to the care of health as to the conservation of the environment. The business team is made up of professionals in the area of Business Administration Francy Elena Londoño, Sandra Milena Pineda López and Elizabeth Yepes García, who have excellent training and knowledge in the elaboration of projects. This project requires a total investment of $ 83,323,246, of which the enterprising women will participate with $ 30,000,000 and the remaining $ 53,323,246 will be contributed by an investor. This business is an opportunity, because the demand for the pulp of fruit is increasing locally, so production will be 139,772 grs / year on average, earning $ 258,886,606 per year for sales of fruit pulp in the presentations of 200grs to $ 1,200, from 250grs to $ 1,600 and 500grs at a price of $ 2,400. The profitability of the 5-year project is 60.3% per year, the present value net of 11.69%, reaching a positive value of $ 132,781,514 during the the recovery of the investment is 1.9 a year with nine months and obtains a point of equilibrium with the production and sales of 131.763grs. pulps a year. Consequently, the viability of the project is demonstrated according to the results of market studies, technical, administrative, economic and for the creation and start-up of the company Frutipulpas del Quindío S.A.S.